Satellite-borne atomic clock based on diffuse laser-cooled atoms - Meng, Yan-Ling; Jiang, Xiao-Jun; Wu, Jing; Ye, Mei-Feng; Cheng, Hua-Dong; Li, Lin; Liu, Liang (Frontiers in Physics, 2022)
The technique of laser cooling of atoms gives an opportunity to improve the performance of atomic clocks by using laser-cooled atoms. The most successful cold atom clock, called the atomic fountain, is now widely used as the primary frequency standard in many labs. The cold atom clock for satellite applications, however, has not been reported so far due to special requirements of space applications. Here, we report the development of an engineering model of a satellite-borne cold atom clock, which satisfied all requirements of in-orbit operation. The core of the clock’s principle is the laser cooling of atoms by diffuse laser lights inside the microwave cavity. The structure of the physics package is presented, and its main parameters are also given. The principle and design of the optical bench are described. The initial test results are presented, and the possible improvements are also discussed.